2011
DOI: 10.1021/ja109621n
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Phase Reactions of the Bare Th2+ and U2+ Ions with Small Alkanes, CH4, C2H6, and C3H8: Experimental and Theoretical Study of Elementary Organoactinide Chemistry

Abstract: The gas-phase reactions of two dipositive actinide ions, Th(2+) and U(2+), with CH(4), C(2)H(6), and C(3)H(8) were studied by both experiment and theory. Fourier transform ion cyclotron resonance mass spectrometry was employed to study the bimolecular ion-molecule reactions; the potential energy profiles (PEPs) for the reactions, both observed and nonobserved, were computed by density functional theory (DFT). The experiments revealed that Th(2+) reacts with all three alkanes, including CH(4) to produce ThCH(2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 74 publications
3
41
0
1
Order By: Relevance
“…The tight convergence criteria and no symmetry restrictions were used during the optimizations. Previous studies have been shown that the main features of actinide complexes can be accurately reproduced at this level of theory [43][44][45].…”
Section: Theoretical Methodsmentioning
confidence: 85%
“…The tight convergence criteria and no symmetry restrictions were used during the optimizations. Previous studies have been shown that the main features of actinide complexes can be accurately reproduced at this level of theory [43][44][45].…”
Section: Theoretical Methodsmentioning
confidence: 85%
“…In this work, intermediate optimization and transition state search were calculated by B3LYP (the Becke's three‐parameter hybrid functional (B3) combined with the Lee‐Yang‐Parr (LYP) correlation functional) method of density functional theory (DFT). It is the most widely used functional and corresponds with experimental value . In addition, for obtaining more reliable structural parameters, M06‐L method also was used.…”
Section: Computation Methodsmentioning
confidence: 99%
“…5f-Orbitalen experimentell und theoretisch untersucht worden. [123] Interessant ist hier der Befund, dass die Insertionseffizienz zur Erzeugung der C-An 2+ -H-oder C-An + -H-Spezies von der Promotionsenergie abhängt, die nçtig ist, um jene elektronisch angeregten Zustände zu erreichen, die zur Bildung zweier kovalenter Bindungen unter Beteiligung von Nicht-5f-Valenzlektronen geeignet sind. [124] Außerdem ist ein Spinwechsel vom Triplett-Grundzustand in den angeregten Singulett-Zustand der Reaktanten erforderlich, um die thermische Dehydrierung von Methan, durch beispielsweise Th 2+ , in einer exothermen Reaktion ablaufen zu lassen.…”
Section: Addendumunclassified